Sandwich Immunoassay for Bioactive Plasma Adrenomedullin. (15th October 2019) - Weber, Julia; Sachse, Janine; Bergmann, Sarah; Sparwaßer, Andrea; Struck, Joachim; Bergmann, Andreas
Abstract: Background: Adrenomedullin (ADM) is a circulating peptide known to regulate vasodilation and vascular integrity. Increased plasma ADM concentrations have been described for several life-threatening conditions, including cardiovascular diseases and septic shock. Reliable methods for the simple quantification of bioactive ADM (bio-ADM) are lacking. Methods: Monoclonal antibodies against the amidated C-terminus and middle portion of bio-ADM were generated and used for the development of a 1-step immunometric assay for the specific quantification of bio-ADM in plasma. The assay was developed in a microtiter plate/chemiluminescence label format with a significantly reduced incubation time. Precision, linearity, specimen stability, and distribution of results in healthy subjects were evaluated. Results: The use of monoclonal antibodies against predetermined epitopes of bio-ADM enabled the development of an assay for the determination of bio-ADM directly in EDTA plasma. Plasma samples were stable for up to 24 h at ambient temperature and over multiple freeze–thaw cycles without loss of immunoreactivity. The assay had a limit of detection of 3 pg/mL and a limit of quantification of 11 pg/mL. The assay exhibited acceptable linearity characteristics and was not influenced by complement factor H, a putative ADM-binding protein. In healthy subjects, bio-ADM concentrations were all above the limit of detection, and approximately half of them were above the limit of quantification. Conclusions: By using monoclonal antibodies with defined epitope specificities, we have developed a simple, rapid, accurate, and sensitive sandwich immunoassay for bio-ADM. The assay is a potentially novel tool to support patient management, particularly in acute care in the field of sepsis and other indications, which are currently being investigated, such as acute heart failure.